Relationship between volatile odorous substances and production of avermectins by Streptomyces avermitilis - Rezanka, T; Sobotka, M; Prell, A; Sigler, K (Folia microbiologica, 2007)
The time course of production of odorous compounds, i.e. geosmin and oxolones, and of avermectins was determined during the cultivation of S. avermitilis in flasks, 1- and 50-L fermentors. The amount of the antibiotics increased with increasing cultivation time up to more than 2 g/L while the concentration of geosmin rose to more than 4 mg/L. Cultivation without reflux condenser resulted in a lower product formation due to the higher stripping of geosmin. A relatively tight correlation was found between the production of geosmin and the production of avermectins. The production of oxolones peaked on cultivation days 3-5, the sum of oxolones being 60 microg/L. Subsequently, the production dropped below a measurable level. This can be explained as being due to the inhibition of oxolone production by geosmin.
Keywords: kinetika; biotechnologie; Fermentation; Volatilization; Ivermectin; Odorants; volatilizace; Naphthols; odoranty; Streptomyces; ivermektin; naftoly; Gas Chromatography-Mass Spectrometry; fermentace; plynová chromatografie s hmotnostně spektrometrickou detekcí; Biotechnology; Kinetics